A Comparative Study of the Negative Automatic Thoughts of the Normal Students and Students Talents - Ahmed Bani Melhem (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to explore the level of automatic negative thoughts among normal and talented students in the Al-Karak Governorate in light of some variables (such as gender, school, branch, and class). The study sample consisted of (605) male and female students (438) normal students and (167) talented students. To achieve this, the researcher developed a study instrument that meets the conditions of appropriate validity and reliability. The results of the study showed that the level of negative thoughts among normal students was moderate and that the level of negative automatic thoughts among talented students was low. It turned out that there were no statistically significant differences of 0.05 ≤α)). Due to the sex variable, statistically significant differences were found (0.05. ≤α) attributable to the branch and for the benefit of the literary, and the existence of differences attributable to the impact of the school and for the benefit of the regular school. The presence of statistically significant differences is attributable to the effect of the class and a second secondary benefit.